1994
DOI: 10.1289/ehp.94102s10137
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of bleomycin-induced lung fibrosis in hamsters by dietary supplementation with taurine and niacin: biochemical mechanisms.

Abstract: Interstitial pulmonary fibrosis induced by intratracheal instillation of bleomycin (BL) involves an excess production of reactive oxygen species, unavailability of adequate levels of NAD and ATP to repair the injured pulmonary epithelium, and an overexuberant lung collagen reactivity followed by deposition of highly cross-linked mature collagen fibrils resistant to enzymatic degradation. In the present study, we have demonstrated that dietary supplementation with taurine and niacin offered almost complete prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…These properties of LA may correct the energy demand deficit in myocytes. Giri et al (1994) have reported that Taurine and Niacin could ameliorate the pathogenesis of bleomycin-induced lung fibrosis with an increase in lung collagen reactivity. They have attributed the replenishment of NAD and ATP to repair the ROS mediated injured pulmonary epithelium as one of the possible mechanisms of protection afforded by niacin.…”
Section: Discussionmentioning
confidence: 99%
“…These properties of LA may correct the energy demand deficit in myocytes. Giri et al (1994) have reported that Taurine and Niacin could ameliorate the pathogenesis of bleomycin-induced lung fibrosis with an increase in lung collagen reactivity. They have attributed the replenishment of NAD and ATP to repair the ROS mediated injured pulmonary epithelium as one of the possible mechanisms of protection afforded by niacin.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most studies that have examined the effect of taurine on the anti-oxidant defenses were initially designed to evaluate its effectiveness in reversing the actions of a toxic xenobiotic. In one such study, Giri et al 40 found that bleomycin increased the activity of superoxide dismutase in hamster lung but the increase was prevented in hamsters fed a diet containing elevated levels of taurine and niacin. Nonetheless, there are a handful of studies that have directly tested the effects of taurine on the anti-oxidant defenses.…”
Section: Anti-oxidant and Membrane Stabilizing Activity Of Taurinementioning
confidence: 99%
“…production 48 • Another important property of N-chlorotaurine is the ability to regulate the severity of the inflammatory response 40 .4 9 ' 50 . Several groups have shown that Nchlorotaurine downregulates the generation of inflammatory mediators, such as superoxide, nitric oxide, tumor necrosis factor-a, interleukin-6 and prostaglandin E2 51 -53 • It also inhibits the expression of chemokines involved in the recruitment of neutrophils into the lung during pulmonary inflammation 54 • Moreover, there is some evidence that taurine may reduce neutrophil activation and adherence to endothelial cells.…”
Section: Anti-oxidant and Membrane Stabilizing Activity Of Taurinementioning
confidence: 99%
“…Besides being the precursor of cofactors to many vital enzymes, nicotinic acid is a drug possessing vasodilating and fibrinolytic properties. Nicotinic acid itself has been proven beneficial against bleomycin-and cyclophosphamide-induced lung injury in animal models (1)(2)(3)(4)(5). Dietary supplements of nicotinic acid and dermatologic formulations of its longchain esters are under investigation for the prevention and treatment of skin carcinogenesis (6).…”
mentioning
confidence: 99%